(3TQM eKdKGJ bWQHs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3eMeO Hf GdeSJfjQ Hf CMeO, CHh Ydj, GdTgjQ HbWQH,J (B206 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdHGQi hHYO JSdje Ydi cd fHi CTQM ai eKdKGJ bWQH CQLhRI TGFbg ai GdeZQH JQhb ai eSGeY GdMVGQ s
(3BNQgG (B:s
(3hGdeWQ GdSGcH agh bWQ Ke GdePGH ef fLGS aWQ Ke GdVjGY hGdHdGO aGdbQ eYQhaI ef ZjQ EfcGQ JeJ GdeKdKI dbWQH eY TQMgG HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B108 - (3U(B111s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B95 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B15s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs